PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Primawati, Dina Aris; Andajani, Andajani (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This research aimed to examine the effect of Corporate Social Responsibility on the firm value of mining companies listed on the Indonesia Stock Exchange (IDX) during 2016-2019. Corporate Social Responsibility based on Global Reporting Initiative (G-4) consisted of 3 performance categories: economic performance, environmental performance, and social performance on the firm value, referred to as Tobin’s. The research was quantitative. The data were secondary, in the form of annual reports. Moreover, the data collection technique used purposive sampling, in which the sample was based on the criteria given. In line with that, there were 26 mining companies listed on the Indonesia Stock Exchange (IDX) during 2016-2019 as the sample. Therefore, in total there were 104 data of observations. Furthermore, the data analysis technique used multiple linear regression. The result concluded that economic performance had a positive effect on firm value. However, the environmental performance had a negative effect on firm value. In contrast, the social performance had a positive effect on firn value.